2012
DOI: 10.1016/j.niox.2012.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Dietary inorganic nitrate alleviates doxorubicin cardiotoxicity: Mechanisms and implications

Abstract: Doxorubicin (DOX) is one of the most powerful and widely prescribed chemotherapeutic agents to treat divergent human cancers. However, the clinical use of DOX is restricted due to its severe cardiotoxic side-effects. There has been ongoing search for cardioprotectants against DOX toxicity. Inorganic nitrate has emerged as a bioactive compound that can be reduced into nitrite and nitric oxide in vivo and in turn plays a therapeutic role in diseases associated with nitric oxide insufficiency or dysregulation. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 96 publications
(125 reference statements)
1
25
0
1
Order By: Relevance
“…Cardiotoxicity is the overriding drawback by which most patients fail to survive even long after the cessation of the drug, leading to degenerative cardiomyopathy and heart failure [2,3]. Doxorubicin-induced cardiotoxicity occurs in two forms: acute and chronic, which occurs in 11 and 1.7 % of cases, respectively [4].…”
Section: Introductionmentioning
confidence: 99%
“…Cardiotoxicity is the overriding drawback by which most patients fail to survive even long after the cessation of the drug, leading to degenerative cardiomyopathy and heart failure [2,3]. Doxorubicin-induced cardiotoxicity occurs in two forms: acute and chronic, which occurs in 11 and 1.7 % of cases, respectively [4].…”
Section: Introductionmentioning
confidence: 99%
“…12 In addition, we recently demonstrated that oral nitrate supplementation protects against doxorubicin-induced cardiomyopathy by improving mitochondrial function. 13,14 Beetroot juice (BRJ) is one of the highest nitratecontaining vegetable products. The consumption of BRJ exerts beneficial effects in healthy volunteers, including lowering of both systolic and diastolic blood pressures, through elevation of cyclic guanosine monophosphate (cGMP) concentration, and protection of the endothelium from I/R-induced endothelial damage.…”
Section: Introductionmentioning
confidence: 99%
“…Supplemental nitrate in the drinking water for seven days increased blood and tissue NO products and significantly reduced infarct size. 10 We recently demonstrated that nitrate supplementation also attenuated cardiotoxicity of doxorubicin -a highly effective anticancer drug 13,14 and the protective effects of nitrate were associated with increase of plasma nitrate-nitrite levels 13 and upregulation of cardiac Prx5. 24 Contrary to our expectation, the present results indicated that the BJR-induced cardioprotection was not associated with significant restoration of plasma concentrations of nitrate and NO x , which were significantly suppressed at the end of I/R ( Figure 5).…”
mentioning
confidence: 99%
“…Top IIb is present in quiescent cells such as cardiomyocytes, and its inhibition by anthracyclines causes DNA double-strand breaks and transcriptome changes (responsible for defective mitochondrial biogenesis) and ROS formation [7]. Knowledge of the molecular mechanisms of anthracycline CTX is fundamental for understanding and selecting pharmacological [8] and non-pharmacological [9,10] strategies for CTX treatment and prevention.…”
Section: Molecular Mechanisms Of Anthracycline Cardiotoxicitymentioning
confidence: 99%
“…Based on preclinical evidence, use of oral nitrate supplementation could be a novel preventive approach for effectively reducing CTX in cancer patients receiving anthracyclines [10]. Also, aerobic exercise is a promising strategy to prevent anthracycline-induced cardiac injury [9,97].…”
Section: The Issue Of Genetic Predispositionmentioning
confidence: 99%